Hubungan Tingkat Pengetahuan Ibu tentang Menyikat Gigi dengan Hasil Menyikat Gigi Anak di Ukur Dengan Plak Indeks - Putri, Novita Nugrahani; Ningrum, Nining; Nurjanah, Neneng; Hendriani Prapptiwi, Yenni (Poltekkes Kemenkes Bandung, 2024)
Brushing teeth is the easiest way to maintain oral health, but there are still many people who ignore the importance of brushing their teeth. The aim is to determine the relationship between the level of parental knowledge about tooth brushing and the results of the Plaque Index of children at Tunas Karya II Kindergarten, Panyairan Village, Cianjur Regency. This type of research is analytical, using the cross sectional method by giving questionnaires to parents and checking the Plaque Index directly to kindergarten children. The sample size was 40 children and 40 parents of Tunas Karya II Kindergarten, Panyairan Village, Cianjur Regency. The results of parents' knowledge about tooth brushing were 62.5% with sufficient criteria, and the results of Plaque Index examination in children were 90% with good criteria. The results of the Kendall's Tau b correlation test showed a significant relationship between the level of parental knowledge about tooth brushing and the results of the Plaque Index of children at Tunas Karya II Kindergarten, Panyairan Village, Cianjur Regency. (P-value = 0.001 <0.05).